An influence of road pricing upon the performance of bus transit services in Oslo - Olga Ivanova (European Regional Science Association (ERSA), 2004)
Discussions of road pricing have paid relatively small attention to the potential effects on the provision of public transport services in a region as depending upon the level of competition in a public transit sector. The present paper uses a fairly simple transport network equilibrium model of the greater Oslo region of Norway in order to investigate the impacts of road pricing upon the performance of bus transit sector. Empirical analysis is performed for the case of publicly and privately owned bus transit including the cases of monopoly, oligopoly and perfect competition. Analysis performed in the paper captures the present state of bus transit in the greater Oslo region as well as its possible future developments.
Keywords: 330